The Role of Anti Corruption: Any Influence of Environmental and External Cost, Carbon Emissions, Employee Turnover, Also Stock Returns to Firm Value - Gunawan, Juniati; Rosady, Gempar (Dinasti Publisher, 2025)
This research aims to examine the influence of Environmental Costs, Carbon Emissions, Employee Turnover, Stock Returns, and External Costs as components of the Environmental, Social, and Governance (ESG) framework on firm value, with Anti-Corruption as a moderating variable. The study focuses on companies in the carbon sector in Indonesia. A quantitative method was used by collecting data through company documentation from those listed in the carbon exchange sector. Data analysis was conducted using multiple regression and moderation techniques. The results indicate that Environmental Costs have a positive impact, Carbon Emissions have a negative impact, and Stock Returns have a significant positive effect on firm value, as measured by Net Profit Margin. In contrast, Employee Turnover, External Costs, and Anti-Corruption do not show a significant effect on firm value. These findings provide useful insights for companies to improve ESG practices and can serve as a reference for regulators and other stakeholders in developing policies that support the growth of carbon sector companies in Indonesia.